Modelagem pedagógica na educação on-line: a influência do modelo pedagógico na sensação de proximidade e distância - Gomes, Renato de Amorim (2013)
This master s thesis presents some reflections on the pedagogical modeling in online education. The study focused on trying to identify what is the influence of the pedagogical model in the sensation of proximity and distance between the subjects in virtual environments for teaching and learning. With this in mind, we sought in some authors the theoretical basis to address the issue, highlighting Behar (2009) and Coll and Monereo (2010) on pedagogical models; Peters (2001), Moore (2007) and Tori (2010) on proximity and distance; Silva (2010) and Mattar (2009) on interactivity; and Merleau-Ponty (1999) and Basbaum (2005) on sensation. In the virtual ethnographic research, based on the orientations from Godoi, Mello e Silva (2006), Hine (2004) and Meister (2011), we observed, in the period between June 2010 and December 2012, the reaction evaluation of six groups of students from an online course of university extension from the Municipal University of São Caetano do Sul (USCS), whose offer took place in two different virtual environments for teaching and learning: a commercial LMS for the first three groups and the Moodle environment for the others. The results revealed that, in the pedagogical architecture - the first of the elements of the pedagogical model, composed by organizational aspects, aspects related to content, technology and methodology there are several interdependent factors that exert an influence on the sensation of proximity and distance, and that in online education the mere availability of technological resources is not a guarantee that there will be proximity between students and teachers, as well as between students and students. We observe that the transactional distance may increase when the structure is maximized in a virtual environment for teaching and learning of a socio-constructivist and interactionist conception (in the case of this study, Moodle) if it offers "expectations" of dialogue between the participants. On the other hand, transactional distance may decrease when the dialogue is expanded in an environment of behaviorist conception (reflected in this study in a commercial virtual environment for teaching and learning) and when the teacher makes use of mechanisms to increase proximity, especially with students who are digital immigrants